Comparison of the Effect of Perennial Energy Crops and Agricultural Crops on Weed Flora Diversity - Feledyn-Szewczyk, Beata; Matyka, Mariusz; Staniak, Mariola (Agronomy (Basel), 2019)
The cultivation of perennial energy crops is a new agricultural system and so there is limited information available on its effects on biodiversity. The aim of this study was to assess the impact of the cultivation of energy crops on the diversity of weed flora and to compare this diversity with that found in crop production systems on arable land. The best habitats for weed flora were created by willow (Salix viminalis), poplar (Populus sp.), false acacia (Robinia pseudoacacia), and perennial grasses (25–30 species), with the exception of reed canary grass (Phalaris arundinacea) (20 species). The lowest diversity and abundance of weed flora were observed on plantations of Virginia mallow (Sida hermaphrodita) and Jerusalem artichoke (Helianthus tuberosus). Weed communities in energy crops included more perennial species (by 11%), ruderal species (by 10%), and those typical for grassland (by 7%) and forests (by 4%), in comparison to arable land. The plantations of energy plants promoted an increase in the density of the invasive species Solidago gigantea (from 1.9 to 6.3 plants m−2 over six years). The introduction of perennial energy crops into an agricultural landscape causes quantitative and qualitative changes in weed flora communities and, therefore, control of the spread of some non-native and invasive species is needed.